Ovarian and uterine functions in female albino rats fed dietary meal supplemented with Mucuna pruriens (L.) DC. seed powder - Ashidi JS; Owagboriaye FO; Lawal OI; Houghton PJ; Efferth T (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2022)
Background: While the reproduction-enhancing property of Mucuna pruriens (MP) seed has been widely studied in males, little is known about this property in females despite the rate at which the seed is consumed by both sexes worldwide. Objective: To determine the effect of MP seed powder in dietary inclusion on ovarian and uterine functions of adult female albino rats. Methods: The rats were randomised into four groups. Group 1 (Control) was given standard rat chow (15g of feed/rat/day only) while groups 2, 3 and 4 were fed diets supplemented with MP seed powder at 0.75 g, 1.5g and 2.25g/day, respectively, for 12 weeks. Serum levels of oestradiol, follicle stimulating hormone, luteinising hormone, ovarian Δ5, 3β- hydroxysteroid dehydrogenase (Δ5, 3β-HSD) and 17 β hydroxysteroid dehydrogenase (17β-HSD) activities, ovarian and uterine peroxidase and tissue cytoarchitectural structures were used as diagnostic markers of reproductive function. Results: Significant increases in the serum level of all hormones including ovarian Δ5, 3β-HSD, 17β-HSD activities, ovarian and uterine peroxidase activities, and improvement of the ovarian and uterine cytoarchitectural integrity of the rats fed MP at 0.75g/day compared to other groups were observed. However, MP at 2.25g/day induced reproductive dysfunction characterised by significant reductions in hormones, uterine and ovarian enzyme activities, severe degenerative cytoarchitectural lesions in tissues. Conclusions: MP seed improves uterine and ovarian functions at a dose level of 0.75g/day, but a higher dose value may be toxic.